2007
DOI: 10.1017/s1041610207005352
|View full text |Cite
|
Sign up to set email alerts
|

A cross-national study of the relationship between elderly suicide rates and life expectancy and markers of socioeconomic status and health care

Abstract: A potentially testable model with five sequential stages was proposed to explain these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
121
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(138 citation statements)
references
References 48 publications
14
121
1
2
Order By: Relevance
“…Although mental disorders based on biological and genetic gender differences are one of the most prominent causes of suicide (Qin et al, 2000;Altemus, 2006;WHO, 2013a), socio-economic factors linked to changes in gender roles could also explain the gender different changes in suicide with increasing male suicide and decreasing female suicide (Hawton, 2000;Zhang et al, 2005;Dombrovski et al, 2008;Karch, 2011). The impacts of economic indices, such as income, bankrupt, economic inequality (Neumayer, 2003;West, 2003;Shah et al, 2009), and social indicators, including divorce, birthrate, family size, female labor force participation, on suicide have been broadly studied (Burr et al, 1997;Chuang et al, 1997;Neumayer, 2003). Unemployment rate as a composite variable for both economic and social factors is also widely investigated (Hamermesh et al, 1974;Chuang et al, 1997;Burr et al, 1997;Neumayer, 2003;West, 2003) .…”
Section: Introductionmentioning
confidence: 99%
“…Although mental disorders based on biological and genetic gender differences are one of the most prominent causes of suicide (Qin et al, 2000;Altemus, 2006;WHO, 2013a), socio-economic factors linked to changes in gender roles could also explain the gender different changes in suicide with increasing male suicide and decreasing female suicide (Hawton, 2000;Zhang et al, 2005;Dombrovski et al, 2008;Karch, 2011). The impacts of economic indices, such as income, bankrupt, economic inequality (Neumayer, 2003;West, 2003;Shah et al, 2009), and social indicators, including divorce, birthrate, family size, female labor force participation, on suicide have been broadly studied (Burr et al, 1997;Chuang et al, 1997;Neumayer, 2003). Unemployment rate as a composite variable for both economic and social factors is also widely investigated (Hamermesh et al, 1974;Chuang et al, 1997;Burr et al, 1997;Neumayer, 2003;West, 2003) .…”
Section: Introductionmentioning
confidence: 99%
“…The very few studies that conducted cross national research found significant variations in suicidal ideation (Eshun, 1999;Weissman et al, 1999;Casey et al, 2008;Shah et al, 2008), with certain European countries demonstrating high rates of suicidal ideation whereas the Caribbean, Central America, and certain Arabic countries demonstrating lower rates of suicidal ideation (Shah et al, 2007). The one study to examine correlates of suicidal ideation from a cross national perspective has argued that a common set of variables independent of the specific country is associated with suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…The four sequential stages in this model were as follows: low elderly suicide rate-low socio-economic society stage; high elderly suicide rate-low socio-economic society stage; high elderly suicide rate-high socioeconomic society stage; and low elderly suicide rate-high socio-economic society stage. This model has subsequently been substantiated to be accurate using cross-sectional data on elderly suicide rates and two separate measures of socio-economic status in cross-national studies (Shah et al, 2008;Shah, 2010). The relationship between socio-economic status and suicide rates followed an inverted Ushaped curve defined by the quadratic equation Y = A + BX − CX 2 , where A, B, and C were constants, Y was the suicide rate, and X was a measure of socio-economic status.…”
Section: The Epidemiological Transition Modelmentioning
confidence: 99%